Filing for corruption: transparency, openness and record-keeping - Cain, Piers (Crime, law and social change, 2001)
The rhetoric of the new development agenda is shaped by democratisation,decentralisation and accountability. The intention is to reassert the role ofthe state but only within the context of involving and working for thepeople. Multilateral and bilateral donor statements are replete withreferences to openness, transparency, accountability and combatingcorruption. This article discusses the rhetoric of such language but then askshow they are to be implemented.What is at issue is that such terms are crucial development goals but,without greater attention to concrete outcomes and processes, may remainrhetoric.